The Pengembangan Kawasan Permandian Alam Lewaja di Kabupaten Enrekang Penekanan Arsitektur Tradisional Duri - Muhammad Rusli; Muhammad Zaki; Andi Muhammad Ikhsan (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
Lewaja Natural Baths is a leading tourist attraction in Enrekang Regency, South Sulawesi, with significant potential for development as a natural tourism destination based on local wisdom. Situated at the foot of the mountains with natural springs, the area offers a beautiful and refreshing atmosphere. However, the current management and facilities do not optimally reflect local cultural identity, particularly traditional Duri architecture. This study aims to formulate a development strategy for the Lewaja Natural Baths tourist area using traditional Duri architecture as a key element in the area's design.The research method used was a qualitative-descriptive approach through field observations, interviews with local communities and traditional leaders, and a literature review of Duri cultural values and traditional architectural principles. The results indicate that the application of traditional Duri architectural elements, such as the roof shape of the Enrekang tongkonan houses, the use of local materials (wood and bamboo), and spatial patterns based on the socio-communal values of the Duri community, can strengthen the area's identity and enhance its tourist appeal.The area's development strategy focuses on integrating local cultural values into the design of tourist facilities, and strengthening cultural-based promotion. With this approach, it is hoped that the Lewaja Natural Baths area will not only develop physically, but also become a symbol of cultural preservation and local economic empowerment.